Optimal Water Allocation: The North Platte River - Tolley, G. S.; Hastings, V. S. (Quarterly Journal of Economics, 1960)
Introduction, 279. — I. Determinants of water value in the basin, 280; how to allocate water between power and irrigation, 280; taking account of delivery losses along a canal, 284; effects of water rights, 288. — II. Allocation between major water uses, 289; competition among eight water uses, 289; below Lake McConaughy, 290; above Lake McConaughy, 291; between the two areas, 291. — III. Conclusion, 292; findings for the North Platte River, 292; further applications, 293. — Appendix on canal losses, 294.